Analysis ofChristoper Vogler’s Heroe’s Journey in The Creator (2023) Film - Elan Adi Sutrisno; Putri Ayienda Dinanti (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
This study examines the construction of heroism in the character of Joshua Taylor in The Creator (2023) using Christopher Vogler’s Hero’s Journey framework. In modern cinema, heroism is no longer limited to physical strength or traditional bravery but is often defined through moral struggle, emotional conflict, and ethical decisions in complex situations. Joshua represents a modern hero whose journey unfolds amid a global conflict between humans and artificial intelligence (AI). This research applies a qualitative descriptive method with a structural mapping technique to analyze Joshua’s narrative progression across the stages of Vogler’s Hero’s Journey. The findings show that Joshua’s heroism is constructed through moral transformation, sacrifice, and his shift from a disillusioned soldier to a protector figure who prioritizes life and empathy over ideology. His journey highlights that modern heroism is rooted in ethical awareness and personal redemption rather than dominance or power, it reflects cinematic developments in depicting heroism that are more relevant to today's social and technological context.